PENGARUH PERSEPSI KUALITAS LAYANAN DAN KEPUASAN KONSUMEN TERHADAP PEMBELIAN KEMBALI KONSUMEN PADA HYPERMART SOLO GRAND MALL DENGAN PERSEPSI PENANGANAN KELUHAN SEBAGAI VARIABEL PEMEDIASI - Mastuti, Endang Tri (Riset Manajemen & Akuntansi, 2010)
This research aimed to test: 1) the influence of service quality perception toward customerâs purchase intention, 2) the influence of customerâs satisfaction toward customerâs purchase intention, 3) the influence of service quality perception toward customerâs purchase intention with perception management of complaint as mediating, 4) the influence of customerâs satisfaction toward customerâs purchase intention with perception management of complaint as mediating This research was conducted in Hypermart Solo Grand Mall with used sample with amount 150 respondent. Sample method with purposive sampling. Data collecting used interview and questioner. The data were analyzed by using multiple regression by SPSS 13.5 software. The results show that: 1) the influence direct of service quality perception toward customerâs purchase intention, 2) the influence insignificant of customerâs satisfaction toward customerâs purchase intention, 3) the influence indirect of service quality perception via perception management of complaint and significant toward customerâs purchase intention, 4) the influence indirect of customerâs satisfaction via perception management of complaint and significant toward customerâs purchase intention, 5) customerâs purchase intention variable explains a service quality perception and a customerâs satisfaction with perception management of complaint as intervening variable is 98.8% and while its remain 1.2% is explained by other variables which are involved in the regression model such as a marketing mix, product and trust, 6) path analysis shows that: a) the service quality perception has direct influence toward the customerâs purchase intention dominant compare the service quality perception has influence toward the customerâs purchase intention via perception management of complaint, b) the customerâs satisfaction has direct influence toward the customerâs purchase intention dominant compare the customerâs satisfaction has influence toward the customerâs purchase intention via perception management of complaint.